Preoperative MRI of Articular Cartilage in the Knee: A Practical Approach - Fritz, Russell C.; Chaudhari, Akshay S.; Boutin, Robert D. (The Journal of Knee Surgery, 2020)
Articular cartilage of the knee can be evaluated with high accuracy by magnetic resonance imaging (MRI) in preoperative patients with knee pain, but image quality and reporting are variable. This article discusses the normal MRI appearance of articular cartilage as well as the common MRI abnormalities of knee cartilage that may be considered for operative treatment. This article focuses on a practical approach to preoperative MRI of knee articular cartilage using routine MRI techniques. Current and future directions of knee MRI related to articular cartilage are also discussed.
Keywords: cartilage; knee; MRI